2010
DOI: 10.1007/s00198-010-1261-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and bone mineral density in adults: a systematic review

Abstract: Limited good quality evidence exists for the role that education level may play in BMD levels. Cohort studies are required to examine the relationship between individual SES parameters and BMD in order to identify potential intervention targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 34 publications
6
49
0
2
Order By: Relevance
“…Low SES, often associated with sub-optimal nutrition and growth delays, may therefore explain the negative correlation between physical activity and LS BMD, a site made up of predominantly trabecular bone, the turnover of which is influenced by the hormonal and metabolic milieu. Low SES has been shown to be a strong independent predictor of whole body bone mineral content, after adjusting for body size and pubertal development in 9-/10-year-old children [22] and adults [35], and has been associated with an increased risk of fracture [36]. Accordingly, we showed that BMD was associated with a higher level of education in black women, which is similar to other studies in the USA [30] and North Africa [37].…”
Section: Discussionsupporting
confidence: 90%
“…Low SES, often associated with sub-optimal nutrition and growth delays, may therefore explain the negative correlation between physical activity and LS BMD, a site made up of predominantly trabecular bone, the turnover of which is influenced by the hormonal and metabolic milieu. Low SES has been shown to be a strong independent predictor of whole body bone mineral content, after adjusting for body size and pubertal development in 9-/10-year-old children [22] and adults [35], and has been associated with an increased risk of fracture [36]. Accordingly, we showed that BMD was associated with a higher level of education in black women, which is similar to other studies in the USA [30] and North Africa [37].…”
Section: Discussionsupporting
confidence: 90%
“…All studies were observational. Grading of the overall evidence based on Brennan et al (2011) confirmed strong evidence for a relationship between HGS and hip fracture incidence ("generally consistent findings in multiple high-quality cohort studies"). It was however not possible to comment on the strength of that relationship, as studies were not comparable with regard to design, analyses, populations, primary objectives and dynamometer brands.…”
Section: Methodological Quality and Strength Of Evidencementioning
confidence: 68%
“…Overall evidence was graded using previously published criteria (Brennan et al, 2011;Lievense et al, 2002) with four levels of evidence (no evidence to strong evidence) based on quality, design and number of included studies (appendix 2). In order to compare HGS measures, values provided in Newton were converted into Kilograms (kg); values provided in Kilopascal (kPa) could not be converted (conversion only possible to Kilogram force per square meter).…”
Section: Critical Appraisal Grading Of Evidence and Data Analysismentioning
confidence: 99%
“…Recent studies are now targeting SEP as a risk factor for poor bone health, raising public health concerns. In these studies [3][4][5][6][7][8], low SEP is associated with low bone mineral density (BMD) and/or increased risk of osteoporosis (or osteoporotic fractures), which may be explained by less protective behaviors in low-SEP individuals. Low SEP can negatively influence bone health and increase the risks of osteoporotic fractures, which deteriorate quality of life [9].…”
mentioning
confidence: 98%